An examination of retailers' compliance with the minimum legal drinking (purchasing) age law in Slovenia: A quasi-experimental intervention study - Kamin Tanja; Čož Sinja; Atanasova Sara (Sciendo, 2021)
Alcohol consumption among young people is strongly related to alcohol availability. The minimum legal drinking (purchasing) age (MLDA) is a legal measure that regulates alcohol availability to minors in Slovenia. This study examines (1) retailers' compliance with the MLDA law in Slovenia and (2) the effectiveness of two interventions directed at cashiers in off-premise stores.